Uniwersytet Zielonogórski w latach 2001-2007 = University of Zielona Góra between 2001 and 2007 - Stankiewicz, Ryszard (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper covers the genesis of the University of Zielona Gora and its functioning between 2001 and 2007. The content includes such areas as the organization of scientific and educational activity (based on faculties, departments, institutes and units) along with the changes it has been subjected to; the authorities and systems of management; the scientific and teaching staff, its development as well as the influence it exerts over categorization and the authority of the departments to grant doctoral and postdoctoral degrees, and the categories those departments are granted.
Keywords: Uniwersytet Zielonogórski; szkolnictwo wyższe